2016
DOI: 10.1186/s12909-016-0802-2
|View full text |Cite
|
Sign up to set email alerts
|

Do photographs, older adults’ narratives and collaborative dialogue foster anticipatory reflection (“preflection”) in medical students?

Abstract: BackgroundIn changing higher education environments, medical educators are increasingly challenged to prepare new doctors to care for ageing populations. The Depth of Field: Exploring Ageing resource (DOF) uses photographs, reflective questioning prompts, older adults’ narratives and collaborative dialogue to foster anticipatory reflection or ‘preflection’ in medical students prior to their first geriatric medicine clinical placement. The aim of this research is to explore whether photographs, narratives and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Another recent mixed method study considered the effect of an innovative anticipatory reflective learning strategy in geriatric medicine curriculum, facilitated for 128 second‐year University of Western Australian medical students . In this study, students were shown photographs, offered older adult narratives and made to engage in collaborative dialogue to foster the reflection on their interactions with older patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another recent mixed method study considered the effect of an innovative anticipatory reflective learning strategy in geriatric medicine curriculum, facilitated for 128 second‐year University of Western Australian medical students . In this study, students were shown photographs, offered older adult narratives and made to engage in collaborative dialogue to foster the reflection on their interactions with older patients.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the study captured a positive shift in student attitudes towards older people after the reflective learning sessions, as measured by statistically significant improvement in eight of the 13 items of a locally adapted UCLA‐GAS instrument, and by qualitative feedback. The authors conclude that ‘The findings demonstrate the importance of facilitating learning opportunities for preflection as they create a safe space for students to begin the developmental process of becoming aware of potential bias, to explore and unpack their thoughts around ageing and integrate this growing awareness into their future clinical experiences and practise with older adults in more mindful ways’ [; p.7,8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-post questionnaire and individual written reflections were collected to explore whether the documentary style photographs and collaborative classroom dialogue fosters reflective learning and has the potential to shift medical student's attitudes towards caring for older adults. The data showed that visual and narrative methodologies (used in DOF) stimulated reflective learning processes that generated a positive shift in medical students' perceptions towards older adults [1].…”
Section: Commentarymentioning
confidence: 99%